Reaching out to the disaffected: mindfulness and art therapy for building resilience to violent extremism. (2nd January 2018) - Taylor, Elisabeth (Lily)
ABSTRACT: Alienation and moral disengagement have been described in the literature as some of the key factors for making some people more vulnerable to violent extremism. In this paper, I explore how mindfulness training, especially when paired with art therapy strategies, has great potential for supporting targeted educational measures for building resilience to violent extremism in individuals and communities.